Pedagogical Analysis of World Experience in Developing Logical Thinking in Students (Eurasian Journal of Learning and Academic Teaching, 2022)
This article describes the relevance of the problem of the development of logical thinking among students and the world experience in solving this problem. In particular, opinions are given on the practical situation of teaching students logical thinking in the education system of such countries as the USA, Japan, and Singapore